2005
DOI: 10.1097/01.mib.0000165114.10687.bf
|View full text |Cite
|
Sign up to set email alerts
|

Ileal Involvement Is Age Dependent in Pediatric Crohnʼs Disease

Abstract: In children, ileal CD lesions are delayed compared with colonic lesions. This observation is in agreement with the previously proposed hypothesis of a pathophysiological role of Peyer's patches in ileal CD. The rarity of small bowel lesions should be a warning to be cautious when classifying chronic colitis in small children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 31 publications
5
49
2
2
Order By: Relevance
“…The number of Peyer's patches increases during childhood and reaches a peak in late adolescence, then it starts to regress (31). This observation may be the link between the lower CRP levels in Crohn colitis.…”
Section: Discussionmentioning
confidence: 90%
“…The number of Peyer's patches increases during childhood and reaches a peak in late adolescence, then it starts to regress (31). This observation may be the link between the lower CRP levels in Crohn colitis.…”
Section: Discussionmentioning
confidence: 90%
“…The phenomenon of age dependence in the phenotypic clinical expression of CD has been reported in some studies. [23][24][25] It is generally believed that CD runs a more aggressive course in young patients. 26,27 Yet the data are still inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…The variable age at diagnosis, that is proper to assess time-dependent consequences of CD, in several studies has been related to disease location, gender, and familial history (10,18,21) . In 1996, Polito et al (21) , analyzing a cohort of 552 consecutive patients, found that a lesser age at diagnosis was associated with higher rates of familial history of CD, small bowel onset, stricturing disease, and surgery; younger age at diagnosis was also correlated with genetic factors (12) .…”
Section: Discussionmentioning
confidence: 99%